Pyogenic Granuloma of Lower Lip: An Unusual Presentation - Rai, Amita; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha; Shrestha, Ashish (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Pyogenic granuloma is a benign inflammatory hyperplasia of connective tissue. It depicts an overzealous tissue response to a known stimulus or injury and is commonly found in the gingiva, especially in the anterior maxilla, and rarely on lips, oral mucosa, and tongue. It is commonly seen during the second, third, and fourth decade in females, with predilection in the third decade. This case report depicts the unusual presentation of pyogenic granuloma of the lower lip in an 11-year-old male child following a positive history of trauma and lip biting, which was successfully managed by excision under local anesthesia.